Numerical simulation of dental bone remodeling induced by implant‐supported fixed partial denture with or without cantilever extension. (19th July 2013) - Wang, Chao; Li, Qing; McClean, Colin; Fan, Yubo
SUMMARY The current study aims to evaluate and compare the bony biomechanical response and possible long‐term restorative consequences stemming from the use of two‐unit fixed partial dentures (FPDs) with or without cantilever configuration. The numerical simulations of bone remodeling were performed using an adaptive strain energy density algorithm, which incorporates an overloading bone resorption process. A patient specific 3D finite element model of a maxillary bone with two absent central incisors was constructed on the basis of clinical computed tomography data. Two different implant‐supported two‐unit FPD models were developed. The simulated remodeling results were visualized by examining the variation of apparent bone density. Different bone responses under normal and overload conditions were compared quantitatively and qualitatively between the cantilever and non‐cantilever models. The mechanical stress/strain distributions were also examined. Furthermore, the simulation results were compared with a similar clinical X‐ray image of the implant site. This study revealed that bone resorption due to overloading was more severe in the cortical neck around the implant‐supported cantilever FPD, as compared with the non‐cantilever configuration, which is better for maintaining the overall health of bone tissue. It is expected that such simulation methodology can be helpful in improving longevity and reliability of future dental implants. Copyright © 2013 John Wiley & Sons, Ltd.